Administração intravítrea de triterpenos como potencial alternativa para o tratamento da uveíte. - Cibele Rodrigues Toledo (2022)
Uveitis is an ocular inflammatory disease affecting both the uveal tract and adjacent structures and is considered a major cause of irreversible vision loss and the third leading cause of blindness worldwide. The initial treatment protocol for non-infectious uveitis is based on the administration of corticosteroids to suppress the inflammatory response. However, long-term use of these therapies is associated with serious adverse effects. Thus, the investigation of new anti-inflammatory agents with potential use in the treatment of uveitis has been stimulated. This study aimed to evaluate the antiangiogenic activity and the safety of intravitreal administration of the triterpenes (TPs) friedelin, friedelinol, lupenone, and lupeol, as well as to investigate the therapeutic efficacy of lupeol and lupenone as anti-inflammatory agents through in vitro assay and a model of experimental uveitis induced by bacillus Calmette-Guérin (BCG) in Wistar rats. Due to the absence of studies concerning the ophthalmic application of TPs, the toxicity assay in a retinal pigmented epithelium cell line (ARPE-19) helped to estimate the dose range to be employed in in vivo assays. Using the chicken embryo chorioallantoic membrane model, TPs with lupane skeleton showed high antiangiogenic potential, being comparable to that of bevacizumab 1 µmol/L. Moreover, lupanes at 100 µmol/L presented the best ratio between the applied dose and obtained result. Through electroretinographic exam and histological evaluation, which are important parameters in the safety assessment of intravitreal administration of new drugs, FA, FL, and LL (at 100 µmol/L) and LA (at concentrations up to 500 µmol/L) showed no evidence of toxic effects on the retina for 15 days, suggesting the safety in the ophthalmic application of TPs. In the sequence, the anti-inflammatory activity of LL and LA (100 µmol/L) was further investigated in ocular tissues, using in vitro and in vivo models. Through the in vitro assay, lupanes reduced the levels of the pro-inflammatory cytokines IL-6 and IL-8, released by ARPE-19 cells in response to stimulation by lipopolysaccharide, and this decrease is comparable to the group that received treatment with the standard dexamethasone. Similarly, the intravitreal injection of the lupanes in rats with uveitis attenuated the severity of inflammation, in both anterior and posterior segments of the eyes, which was confirmed by clinical, electroretinographic, histopathological, and immunological analyses. Therefore, the intravitreal administration of LA and LL at 100 µmol/L is a promising therapy for the management of uveitis.